Unilateral Aplasia of the Middle Cranial Fossa Floor in Atypical Hemifacial Microsomia - Sze, Raymond W.; Gruss, Joseph S.; Cunningham, Michael L. (American Journal of Neuroradiology, 2001)
Summary: We present the first report of a patient with atypical hemifacial microsomia (HFM) and unilateral aplasia of the floor of the middle cranial fossa, glenoid fossa, and portions of her posterior fossa. The patient also developed a Chiari I malformation with cervical syrinx over a 3-year interval. This case report highlights the critical role of imaging in revealing serious, but clinically occult, structural abnormalities, as well as the evolution in the pathogenetic understanding of HFM.